The Influence Of Organizational Commitment On Employee Performance - Nurcahya Hartaty Posumah; Irwan Moridu (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This study's objective is to assess the expenses and logistics coordinator for the kinerja karyawan hotel in Makassar. The respondent to this study is a hotel karyawan located in Makassar. Seberita 55 responden dilakukan antara Jumlah Responden Penelitian ini. The sampling process was conducted using the purposive sampling technique. The present study employed the regression analysis technique with SPSS as the backtesting software. Based on the collected data, it can be concluded that the parsimal kerja ketuasan has a significant impact on the kinerja of the hotel karyawan in Makassar. The organizing committee of the parsimal Komitmen di Makassar incurred a significant loss in terms of clientele. Kepuasan kerja dan komitmen organisasi secara simultanis karyawan hotel kinerja di Makassar berpengaruh signifikan.